PPP6R3‐USP6 amplification: Novel oncogenic mechanism in malignant nodular fasciitis. Issue 8 (30th May 2016) - Guo, Ruifeng; Wang, Xiaoke; Chou, Margaret M; Asmann, Yan; Wenger, Doris E.; Al‐Ibraheemi, Alyaa; Molavi, Diana W; Aboulafia, Albert; Jin, Long; Fritchie, Karen; Oliveira, Jennifer L.; Jenkins, Robert B.; et al.
Abstract : Nodular fasciitis (NF) is a clonal self‐limited neoplastic proliferation characterized by rearrangements of the USP6 locus in most examples. To our knowledge well‐documented malignant behavior has never been previously observed in NF. In this report we present an unusual case of NF with classical histologic features that showed a protracted clinical course characterized by multiple recurrences and eventual metastatic behavior over a period of 10 years. Molecular analyses revealed the presence and amplification of the novel PPPR6‐USP6 gene fusion, which resulted in USP6 mRNA transcriptional upregulation. These findings further support the oncogenic role of the USP6 protease in mesenchymal neoplasia and expand the biologic potential of NF. © 2016 Wiley Periodicals, Inc.